2016
DOI: 10.1186/s40200-016-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Type II diabetes and personality; a study to explore other psychosomatic aspects of diabetes

Abstract: BackgroundAs one of the most common chronic diseases, diabetes and its control are affected by the patients’ psychological and spiritual attributes. The present study investigates the relationship between glycemic control in patients with type II diabetes and personality traits, defense mechanisms and spirituality.MethodThe present cross-sectional study was conducted on 400 Iranian patients with type II diabetes, 64% were men. Participants completed the NEO Personality Inventory, the Defense Style Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 14 publications
2
46
1
Order By: Relevance
“…21 On the other hand, a positive relationship between HbA1c and neuroticism has been suggested in Iran, although confounding factors were not controlled. 22 Previous studies have shown that extraversion is consistently and inversely associated with HbA1c in Korean patients, 17 Iranian patients 22 and American patients 19 with T2DM. However, we failed to find this association.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…21 On the other hand, a positive relationship between HbA1c and neuroticism has been suggested in Iran, although confounding factors were not controlled. 22 Previous studies have shown that extraversion is consistently and inversely associated with HbA1c in Korean patients, 17 Iranian patients 22 and American patients 19 with T2DM. However, we failed to find this association.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies tried to find some associations between glycemic control and Five-Factor Model personality using simple regression model, which showed inconsistent results. [16][17][18][19][20][21][22] However, few studies have examined the comprehensive links using multifactor analysis, including lifestyle factors and psychological problems such as depression and insomnia, between the Five-Factor Model and glycemic control among individuals with chronic T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Novak et al studied 117 couples with diabetes and demonstrated that neuroticism reduces dietary and exercise Journal of Diabetes Research adherence and is therefore associated with lower diabetic efficacy [41]. Similarly, an Iranian study of type 2 diabetic patients reported neuroticism to be positively correlated with poor glycaemic control, while extraversion and conscientiousness were inversely correlated [42]. In addition, an Australian study of type 1 diabetic patients also reported that conscientiousness and agreeableness are significant predictors of good glycaemic control [43].…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to determine the psychosocial factors that might influence effective adherence to medical recommendations in diabetic patients described in the literature. 12 14 The patient’s appropriate attitude toward the disease is of particular significance in this context. Health psychology defines the attitude toward a disease in three dimensions: cognitive (the patient’s knowledge about the disease and treatment process), emotional (emotions the patient experiences regarding the disease), and behavioral (actions taken by the patient with respect to the disease and treatment process).…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 16 , 18 A considerably greater number of studies have analyzed the relationship between psychological factors and adherence to dietary recommendations. 6 8 , 12 , 17 Also, there are no papers researching the role of mediating factors in this relationship, where they are related directly to the treatment of diabetic patients. Therefore, the aim of this paper was to analyze the relationship between selected independent variables (eg, blood glucose testing, occurrence of complications, and doing enough physical activity) and the level of the patient’s compliance with dietary recommendations, considering the mediation role of the patient’s level of disease acceptance.…”
Section: Introductionmentioning
confidence: 99%